'Réprimer le désordre': Prostitution, Regulation and the Poetics of Realism in Balzac and Sand. (1st January 2011) - Wilson, Steven
This article examines the textual representation of the prostitute in two nineteenth-century French authors — Balzac and Sand. It argues that the trope of prostitution — with its links to concepts of control, regulation and power in Balzac's work, and subversion, disorder and liberation from repressive plot structures in Sand's — constitutes a privileged motif by which to read realism and its counter-discourses in the nineteenth century.